Ecological momentary assessment of targeted and non‐targeted symptom changes in clinical anxiety and irritability among children and adolescents receiving cognitive behavioral therapy - Lauren M. Henry; Meghan E. Byrne; Julia Modell; Lili Massac; Krystal Lewis; Simone Haller; Reut Naim; Katharina Kircanski; Daniel S. Pine; Melissa A. Brotman (JCPP Advances, 2026)
Abstract Background Decades of youth psychotherapy research have demonstrated the efficacy of cognitive behavioral therapy (CBT) on targeted symptoms using standardized, retrospective clinician‐, child‐, and parent‐report. Advancements in digital technologies can be leveraged to capture granular symptom change in patients' natural environments. While CBT is tailored to treat specific diagnosis‐perpetuating mechanisms, it remains unknown whether such effects may carry over to non‐targeted symptoms, which could have important treatment implications. Methods We examined targeted and non‐targeted symptom change in two separate exposure‐based CBT trials: one trial for anxiety ( n = 92) and one for irritability ( n = 39). Youth in both trials completed ecological momentary assessment (EMA) pre‐, mid‐, and post‐treatment; n = 57 healthy volunteer youth completed EMA at matching time intervals. Each EMA interval lasted for 7 days (3 prompts/day). We used multilevel modeling to examine changes in symptoms across time (e.g., pre, mid, post). Results We observed frustration to decrease over time in both youth with anxiety (non‐targeted symptom) and irritability (targeted symptom). We observed anger to decrease in youth with irritability only (targeted symptom), and worry did not change significantly over time in either group. Healthy volunteer youth showed low, stable levels of symptoms across time. Conclusion Findings highlight frustration as a potential key transdiagnostic symptom; frustration improves in both youth with clinical anxiety and with irritability over the course of exposure‐based CBT. Demonstrating specificity, anger in youth seeking treatment for irritability, but not anxiety, improved over time. While additional research is needed to better understand measurement of in vivo worry, results support using EMA to monitor symptom change during CBT.